Influence of thermochemical reduction on magnetic properties of reduced graphene oxide aerogels. (April 2021) - Tadyszak, Krzysztof; Scheibe, Błażej; Ostrowski, Adam; Musiał, Andrzej; Wychowaniec, Jacek K.
Abstract: The application of two-dimensional (2D) materials as a building component for aerogels formation allows obtaining three-dimensional (3D) structures featured by remarkable physiochemical properties. One of the most commonly applied 2D materials for the aerogels fabrication is a graphene oxide (GO), which can undergo chemical or thermal reduction forming a reduced graphene oxide (rGO) porous network. Interestingly, the influence of the reduction process on the magnetic properties of rGO-based aerogels is still uncharted. This article sheds a light onto interdependence between reducing agents (hydrazine, sodium borohydride, ethane-1, 2-diamine, citric acid, ascorbic acid), which were applied during GO hydrothermal reduction, and the magnetic properties of thereby formed rGO aerogels. The magnetic characterization was performed by vibration magnetometer (VSM) and electron paramagnetic resonance (EPR) in the temperature range of 4–300 K. It was found that the choice of reducing agent significantly affects the resulting magnetic properties of aerogels. This is directly linked to the spatial organization of the defects and localization of conduction electrons in rGO hexagonal lattice. Graphical abstract: Image 1 Highlights: Analysis of unusually high normalized magnetic susceptibility measured by Electron Paramagnetic Resonance. Anderson localization in reduced graphene oxide samples. Influence of reducing agents on the EPR parameters e.g. g-factor, normalized intensity, linewidth. Magnetic properties (EPR, VSM) of chemically reduced graphene oxide.